STRATEGI ADAPTASI SOSIAL EKONOMI RUMAH TANGGA SOPIR ANGKOT (ANGKUTAN KOTA) “TERMINAL NANGKA – SIMPANG PANAM” DI KOTA PEKANBARU - Putri, Mulyati; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This Research entitled "Social Economic Strategic Adaptation Of Household City Transport Driver (Angkutan Kota) “Nangka – Simpang Panam Station” In Pekanbaru City is due to public transportation driver as one of the profession of infomal sector in the field of transportation service experiencing socio-economic problems, especially Fulfill family needs. Their income what is not enough and unprdictable make them as poor household. Their little income make them can’t to fulfill their household needs, so they must implement adaptation strategic for survival their household with limited ability. The problems of this research is How model Social economic adaptation of city transport Driver Station Nangka Simpang Panam in Pekanbaru city and how is dominant model by Social economic adaptation of city transport Driver Station Nangka Simpang Panam in Pekanbaru city. The aim of this research is to explain about model Social economic adaptation of city transport Driver Nangka Simpang Panam Station in Pekanbaru city and to description about dominant model. This research conclusion is three strategic who implemented by city transport Driver households to survival their live. That strategic are active strategic, passive strategic and network strategic. Active strategic are find site job, selling a goods,family members are working, increasing work hour, be a rental driver and they rent their car for other people. Passive strategic is survival strategic who they implement like life saving pattern. A little income make them to minimize their households expens. They eat with simple dishes. Network strategic who implement by city transport Drivers to survive their households live are loan a money to family or neighbour, “jula-jula” and use relation for find site job, cooperative etc. Dominan strategic who implement by city transport driver is passive strategic.Kata Kunci: Social Economic Adaptation Strategic, Survival, City Transport Driver